2022
DOI: 10.1182/blood.2021015135
|View full text |Cite
|
Sign up to set email alerts
|

The genetic landscape of germlineDDX41variants predisposing to myeloid neoplasms

Abstract: Germline DDX41 variants are the most common mutations predisposing to acute myeloid leukemia (AML)/myelodysplastic syndrome (MDS) in adults, but the causal variant (CV) landscape and clinical spectrum of hematologic malignancies (HM) remain unexplored. Here, we analyzed the genomic profiles of 176 HM patients carrying 82 distinct presumably germline DDX41 variants among a group of 9,821 unrelated patients. Using our proposed DDX41 specific variant classification, we identified features distinguishing 116 HM pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 37 publications
5
48
1
Order By: Relevance
“…DDX41 mutations occur at a rate of 2 to 5% in AML (9,10). Most affected patients are in their 60s and are therefore not markedly different to non-DDX41 mutant sporadic AML cases with regard to peak age of disease diagnosis.…”
Section: Clinical Features Of Myeloid Malignancies With Ddx41 Mutationsmentioning
confidence: 96%
See 2 more Smart Citations
“…DDX41 mutations occur at a rate of 2 to 5% in AML (9,10). Most affected patients are in their 60s and are therefore not markedly different to non-DDX41 mutant sporadic AML cases with regard to peak age of disease diagnosis.…”
Section: Clinical Features Of Myeloid Malignancies With Ddx41 Mutationsmentioning
confidence: 96%
“…There does not appear to be a bias toward a specific AML subtype, but the disease is often characterized by low peripheral WBC counts and bone marrow hypoplasia, and a less differentiated tumor cell phenotype. However, there have been no reports of specific mutations in other genes that could contribute to these features of DDX41 mutant AML (9). DDX41 mutations are also observed in acute erythroid leukemia and lymphoid malignancies (23)(24)(25).…”
Section: Clinical Features Of Myeloid Malignancies With Ddx41 Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, remarkable ethnic deviation was found in the mutation sites in DDX41; however, second hit was predominantly R525H, irrespective of ethnicity (47)(48)(49). TP53 and ASXL1 somatic mutations are recurrently detected (48), although the prognostic impact of concomitant mutations is limited (50).…”
Section: Ddx41mentioning
confidence: 99%
“…AML with germline DDX41 mutations has unique clinical characteristics, such as approximately 3:1 male predominance, frequent absence of family history, and indolent clinical course (18,50,51). Makishima et al reported that the age of progression in individuals with germline DDX41 mutation was solely greater than 40 years, and penetrance of pathogenic DDX41 germline variants was estimated to be 38.5% at the age of 85.…”
Section: Ddx41mentioning
confidence: 99%